Creating Systems-Level Change to Better Support Expectant and Parenting Young People: A Case Study. - Purington, Amanda; Stupp, Erica; Sebuharara, Divine; Maley, Brian; Henderson, Sara Birnel; Powers, Jane (Maternal & Child Health Journal)
Introduction: Expectant and parenting young people (young parents) require diverse services to support their health, educational success, and family functioning. Rarely can the needs of young parents be met by a single school or service provider. This case study examines how one large school district funded through the pathways to success initiative was able to facilitate systems change to increase young parents' access to and use of supportive services. Methods: Data sources include a needs and resources assessment, quarterly reports documenting grantee effort, sustainability plans, social network analysis, and capstone interviews. All data sources were systematically reviewed to identify the existing context prior to the start of the initiative, the changes that resulted from the initiative, and efforts that could potentially be maintained beyond the grant period. Results: The community context prior to Pathways implementation was one of disconnected services and missed opportunities. The full-time program coordinator hired by the district focused on systems-level change and facilitated connections between organizations. This greater connectivity contributed to increased collaboration with the goal of producing lasting benefits for young parents. Discussion: Promoting sustainable connections and collaboration at the systems level can help dismantle barriers to service access and benefit young parents.